Multirotor Drones in Topographic Surveys of Mountainous Areas - Erazo Hernández, Ramiro Humberto (2023)
The use of drones in topography is a technology that is being developed and in the first instance the use of this technology was established only for flat areas because the applications available to carry out the flights carried out only horizontal flights and when changing the height of the flight changes the GSD of the generated photograph.   These conditions generated doubts and uncertainty for the use of this technology in topographic surveys of mountainous areas, but with a broader knowledge of these procedures and using the appropriate tools, the drone is a great ally in mountain topographic surveys.   As Quito is a city that is surrounded by mountains and crossed by streams, the use of devices in places of difficult accessibility is very favorable, in this case the use of drones not only for inspection but also for field data collection.   Next, the execution of topographic surveys in mountain areas will be detailed, highlighting that the procedure is similar to that carried out on flat terrain, differing only in flight planning, due to the applications that will be used for a flight at different heights.